Pengaruh Sistem Informasi Akuntansi, Sistem Pengendalian Internal Terhadap Kinerja Karyawan Dengan Insentif Karyawan Sebagai Variabel Moderasi - Sundari, Evi; Hendri, Nedi; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze the Effect of Accounting Information Systems 1; and Internal Control System 2; Against Employee Performance with Employee Incentives 3; As a Moderating Variable at BMT Satria Nuban Muamalah. The type of research used in this study is quantitative with a descriptive approach, in this study researchers used primary data through questionnaires and the population in this study amounted to 25 employees, then the sampling technique in this research used purposive sampling. The research data used SPSS version 26 software. The results of this study indicate that the Accounting Information System has a positive and significant effect on employee performance, the Internal Control System has no effect on employee performance, and employee incentives moderate the accounting information system on employee performance, and employee incentives moderate the internal control system on employee performance at BMT Satria Nuban Muamalah.